The Anxiety of Learning English by Senior High School Students in Medan - Susi Ekalestari (Proceedings of AICS - Social Sciences, 2017)
This study is a result of a research on the anxiety of learning English by students of Senior High School in Medan, North Sumatra. Anxiety is “one form of emotional problem that could highly affect the academic performance of EFL” (Sadiq, 2017). This study is aimed to know the anxiety level of the students of Senior High School in Medan, North Sumatra in learning English as a foreign language, which, then, there will be further research to respond the findings in this study. The further research might be in the form of solution, improvement, modification, and module invention in relation to teaching English as foreign language. The method used in the study is qualitative descriptive method, in which the finding is presented in the form of description of the simple calculation of the data obtained from the questionnaire. This study takes the students of Senior High School in two schools for its respondents. They are the fresh students in 2017. Questionnaires are shared to collect the data related to learning anxiety of English language. The questions in the questionnaire are created to get not only the anxiety level of the students in learning English, but also their obstacles, suggestion and hope to successfully learn English as a foreign language. It is found that the anxiety of learning English experienced by the students of Senior High School is at the moderate level. It reaches 44 respondents (55%) of the whole respondents. The whole respondents are 80 fresh students of Senior High School.